Solusi Digital Audiobook untuk Meningkatkan Minat Baca di SDN 04 Marisa - Muhammad Wahyuddin S. Adam; Anita Wati Tukloy; Maryam Kune; Alfinka Laya; Marjan Rasyid; Mitasari Mitasari; Meysaraswati Biko (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
The use of digital audiobooks as a solution to enhance reading interest among students has become a significant focus in modern education. Audiobooks offer an innovative way to access literature, with advantages including flexibility and ease of technology use. This study examines the impact of audiobook usage on students' reading interest, highlighting how this medium can accommodate various individual characteristics and learning preferences. The results indicate that audiobooks not only enrich the reading experience by presenting lively voices and intonations but also make reading materials more engaging and accessible for students with special needs. Furthermore, an individualized approach to implementing audiobooks, which involves collaboration among teachers, parents, and students, has proven effective in creating a supportive learning environment.